Film Hero—Past, Present, and Future: A Multidimensional Image / Телегерой — прошлое, настоящее и будущее: многомерность образа - LIKHOVTSEVA ANASTASIA V. / ЛИХОВЦЕВА А.В.; ANANISHNEV VLADISLAV V. / АНАНИШНЕВ В.В.; PRONIN MIKHAIL A. / ПРОНИН М.А. (Наука телевидения)
In the article, we consider the image of a movie hero from the perspective of its multidimensionality, as well as the systemic nature of its influence—in the past and in the present. The researched segment of material allows us to present the universal matrices, according to which the image of the hero of the future is constructed. Different stages and epochs of civilizations in various cultures are marked by seminal, iconic ideals, many of which represented and/or personified the status of a hero. The image of a hero has been interpreted in all sorts of ways and transformed through a variety of forms of visualizations. In this paper, we consider a hero in the context of understanding the specificity of a film hero. The image of a “hero of the day” consolidates and refracts a complex of ideals, preferences and perceptions, the model and style of behavior, which are characteristic not only for a particular historical period, but also for a particular community. The phenomenon and concept of a hero and, as a consequence, the image of this hero, has a logically explainable structure, a pattern of formation and becoming. This pattern is interconnected with historical, social, cultural aspects and phenomena, as well as perceptions characteristic for a particular time and society. The character, the image, the style and the model of behavior of the hero, as well as the criteria of his or her assessment depend on the complex of spiritual culture of a particular community, the level of its development and value orientations. The specifics of age-old composition of the images of “a hero of the old/present days” reveal some regularities—universal anthropological constants, allowing to form a set of distinctive qualities of a hero actual for the specific time and location. In this article, we trace such consistent patterns and introduce the typology of four universal atemporal types of heroes (masculine, intellectual, warrior, superhuman), aimed at different audiences. Статья посвящена рассмотрению многомерности образа телегероя и системности его воздействия — в прошлом и настоящем. Предложенный авторами исследовательский срез дает возможность представить универсальные матрицы, по которым выстраивается образ героя будущего. Разные этапы и периоды цивилизаций, а также культуры народов отмечены знаковыми культовыми идеалами, многие из которых являли и/или олицетворяли статус героя. Образ героя был по-разному интерпретирован и преобразовывался через многообразные формы визуализаций. В настоящей работе герой рассмотрен в контексте понимания специфики телегероя. В «герое времени» консолидируется и преломляется сложный комплекс идеалов, предпочтений и представлений, модель и стиль подобающего поведения, характерных не только для определенного исторического периода, но и для конкретной общности. Явление и понятие «герой» и, как следствие, образ этого героя, имеет логично объяснимую структуру, закономерность формирования и становления, взаимосвязанную с историческими, социальными, культурными факторами и явлениями, а также характерными представлениями для конкретного времени и общества. Характер, образ, стиль и модель поведения героя, как и критерии его оценки, зависят от комплекса духовной культуры конкретной общности, уровня развития и ценностных ориентиров. Специфика многовековых построений образов «героя своего/нашего времени» обнаруживает ряд закономерностей — универсальных антропологических констант, что позволяет формировать набор актуальных для места и времени характерных качеств героя. Авторами статьи прослеживается закономерность и вводится типология существования четырех универсальных вневременных типов героев («маскулинный», «интеллектуальный», «воин», «сверхчеловек»), ориентированных на разную аудиторию.